Prior goal setting of SDGs based on the interaction correlation - Zhao, Mingxi; Meng, Zixiang; Xu, Boda; Yu, Dian; Wu, Shu; Li, Rende (Frontiers in Sustainability, 2023)
For 2030, the Agenda for Sustainable Development sets out 17 goals for sustaining ecological and social growth, known as the Sustainable Development Goals (SDGs), which have mobilized countries around the world to integrate these goals into their national development strategies. However, the Agenda does not explain how these goals are interlinked, which limits their implementation. This paper therefore selects indicator data for 17 SDGs from the World Bank website for four groups of countries to estimate the network structure of the SDGs and the synergies and trade-offs between them, based on the Spearman coefficient. Based on this, the paper further uses a VAR model to identify priority targets among the SDGs and to predict the impact of achieving these targets two years earlier on other SDGs. It is found that the SDGs interact with each other in different historical periods, showing both synergies and trade-offs. And as the highest priority goal, the predictions in this paper suggest that SDG 6 has a strong positive impact on SDG 4 and SDG 8. This paper can help policy makers to allocate resources more effectively, maximize benefits, coordinate actions, adapt to future challenges and achieve global sustainable development goals.